Inhibiting xCT/SLC7A11 induces ferroptosis of myofibroblastic hepatic stellate cells but exacerbates chronic liver injury. (4th July 2021) - Du, Kuo; Oh, Seh Hoon; Dutta, Rajesh K.; Sun, Tianai; Yang, Wen‐Hsuan; Chi, Jen‐Tsan; Diehl, Anna Mae
Abstract: Background & Aims: The outcome of liver injury is dictated by factors that control the accumulation of myofibroblastic (activated) hepatic stellate cells (MF‐HSCs) but therapies that specifically block this process have not been discovered. We evaluated the hypothesis that MF‐HSCs and liver fibrosis could be safely reduced by inhibiting the cysteine/glutamate antiporter xCT. Methods: xCT activity was disrupted in both HSC lines and primary mouse HSCs to determine its effect on HSC biology. For comparison, xCT expression and function were also determined in primary mouse hepatocytes. Finally, the roles of xCT were assessed in mouse models of liver fibrosis. Results: We found that xCT mRNA levels were almost a log‐fold higher in primary mouse HSCs than in primary mouse hepatocytes. Further, primary mouse HSCs dramatically induced xCT as they became MF, and inhibiting xCT blocked GSH synthesis, reduced growth and fibrogenic gene expression and triggered HSC ferroptosis. Doses of xCT inhibitors that induced massive ferroptosis in HSCs had no effect on hepatocyte viability in vitro, and xCT inhibitors reduced liver fibrosis without worsening liver injury in mice with acute liver injury. However, TGFβ treatment up‐regulated xCT and triggered ferroptosis in cultured primary mouse hepatocytes. During chronic liver injury, xCT inhibitors exacerbated injury, impaired regeneration and failed to improve fibrosis, confirming that HSCs and hepatocytes deploy similar mechanisms to survive chronic oxidative stress. Conclusions: Inhibiting xCT can suppress myofibroblastic activity and induce ferroptosis of MF‐HSCs. However, targeting xCT inhibition to MF‐HSCs will be necessary to exploit ferroptosis as an anti‐fibrotic strategy.